Malaysia prihatin: sustainability of unity through the cultivation of knowledge, moral and social activism - Kamaruzzaman, Kazzman (2021)
The Malaysia Day 2021 celebration, themed ‘Malaysia Prihatin,’ is the primary ambition and commitment to maintaining the country’s unity and the spirit of patriotism. ‘Malaysia Prihatin’ is not just merely a yearly national theme, as it comprises the country’s vision and desire to develop Malaysian citizens who are equipped with unique personal and national identity. This includes patriotism, empathy, tolerance, mutual respect, and responsibility, all of which demonstrate the values ​​and criteria of human capital development.